PENGARUH TATA KELOLA PERUSAHAAN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE - Sophia Novela; Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims at how the role of board size, board composition, and shares concentration towards intellectual capital disclosure on manufactured industry listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 111 companies. Data processing techniques using multiple regression analysis what helped by E-Views program (Econometrical Views) 12 Student Version (SV) Lite. The results of this study indicate that board composition and shares concentration have a significant influence on intellectual capital disclosure. The implication of this study is the need to increase the role of board composition and shares concentration that will increase the intellectual capital disclosure in the annual reports which will bring a good signal for investors.